Effective Demand versus Profit Maximization in Aggregate Demand/Supply Analysis from a Dynamic Perspective - Amit Bhaduri; Kazimierz Laski; M. Riese (The Vienna Institute for International Economic Studies (wiiw), 1998)
This paper analyses the dynamic interaction between profit maximization and aggregate demand through two alternative theories of price and output adjustment. According to the neoclassical interpretation, excess aggregate demand drives up price, which in turn reduces the real wage rate to induce profit-maximizing firms to produce more. In the alternative view, excess demand generates non-price signals like longer order books or decumulation of inventories inducing firms to produce more. This affects marginal cost at higher production. Firms experiencing decreasing returns in the short period in a competitive market cover higher marginal cost through upward price adjustment, making real wage an outcome, but not a determinant of the output level. The disregard of this latter view has led to logically inconsistent constructions like aggregate demand/supply analysis of many recent textbooks, and a misleading 'monetarist' interpretation of the Phillips curve.
Keywords: A10; B41; E12; E13; 330; Aggregate demand (AD); aggregate supply (AS); concept of derived aggregate demand (DAD); aggregate demand versus profit maximization; output versus price adjustment